Kinerja Pusat Pertanggungjawaban Rumah Sakit dalam Perspektif Balanced Scorecard - Andi Nurcahya; Suryo Pratolo (Universitas Muhammadiyah Yogyakarta, 2017)
This research object being studied are representative of each of the staff of the hospital. The number of respondents in this study were as many as 30 of the 38 respondents in this hospital were sampled by simple random sampling which will then be asked to fill out questionnaires related to the five variables studied in this study. According to the research found that the leadership competencies and positive effect on employee satisfaction. Furthermore, job satisfaction has positive influence on employee performance are also positively affects employee performance accountability hospital center performance with the balanced scorecard perspectives. in addition, also found that the competence and leadership have a direct positive effect on the performance of responsibility centers hospital with balanced scorecard perspectives.